2016
DOI: 10.1002/adsc.201600987
|View full text |Cite
|
Sign up to set email alerts
|

Dual Gold Catalysis: Synthesis of Fluorene Derivatives from Diynes

Abstract: Abstract1,5‐Diyne systems bearing one terminal and one benzyl‐ or allyl‐substituted alkyne attached to an aromatic backbone were converted in the presence of a gold catalyst. In a dual gold‐catalyzed process, gold vinylidenes are formed that selectively undergo formal CH insertion into the C(sp2)–H bond of the offered unsaturated systems. If H atoms are present in the propargylic position, a subsequent isomerization to the aromatic system takes place leading to 9H‐fluorene and 11H‐benzo[b]fluorene derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…[69,70,[79][80][81][82][71][72][73][74][75][76][77][78] In the majority of homogeneous Au catalysts, Au exists in the + 1 oxidation state. [103][104][105][106][107] In the past, the applications of Au I in enantioselectiver eactions have been considered challenging. The relativistic effects cause the contraction of 6s and 6p orbitals andt he expansion of 5d orbitals in Au I .…”
Section: Introductionmentioning
confidence: 99%
“…[69,70,[79][80][81][82][71][72][73][74][75][76][77][78] In the majority of homogeneous Au catalysts, Au exists in the + 1 oxidation state. [103][104][105][106][107] In the past, the applications of Au I in enantioselectiver eactions have been considered challenging. The relativistic effects cause the contraction of 6s and 6p orbitals andt he expansion of 5d orbitals in Au I .…”
Section: Introductionmentioning
confidence: 99%
“…In order to explore the reaction scope, substrates 1 a – q were prepared through a very short sequence, the Sonogashira coupling of 2‐iodobromobenzene with terminal propargylic alcohols at room temperature, followed by oxidation and further coupling with terminal alkynes at 60 °C in the presence of Pd(OAc) 2 /XPhos (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
“…Another example by Hashmi et al was reported in 2017 and was highlighted as the first intramolecular trapping of dually gold-activated intermediates 176 with an olefinic C(sp 2 )-H bond (Figure 15B). 1,5-Diynes bearing an allyl-substituted alkene attached to an aromatic skeleton ( 175 ) could also be converted into fluorene derivatives 177 via a dehydrogenative dual gold-catalyzed activation at reflux of tetrahydrofuran (Bucher et al, 2017). In this sense, dual-gold catalysis has been implemented in the cycloaromatization of unconjugated (E) -enedynes 178 toward isoindolines 181 by using the trigold oxo complex [(Ph 3 PAu) 3 O]BF 4 as catalyst (Figure 15C).…”
Section: Gold-catalyzed Isomerization Processes Involving An Initimentioning
confidence: 99%